In-vitro transcriptomic profiling of indigenous Gaddi vis-à-vis exotic Labrador dogs: insights from systems biology - Kaur, Jaswinder; Mohan, Manu; Singh, Bilawal; Sethi, Ram Saran; Narang, Deepti; Kaur, Simarjeet; Mukhopadhyay, Chandra Sekhar (Frontiers in Veterinary Science, 2025)
IntroductionThe domestication of dogs is regarded as an evolutionary adaptation influenced by artificial selective pressures, leading to the fruition of diverse canine breeds across regions. Indigenous breeds, developed in tandem with local environments, display unique conformations and disease resistance, yet many remain understudied at the molecular level. The Gaddi dog, originating in the northern parts of India and used by local tribes for livestock guarding, exemplifies such a breed with potential for transcriptomic research. Despite its vital role, it remains unrecognized by the National Bureau of Animal Genetic Resources (NBAGR). This study addresses the gaps in understanding the genetics and immune responses of Indigenous breeds, emphasizing their importance as holders of unique genetic heritage. This study explores the molecular profiles of Indigenous Gaddi dogs and exotic Labrador retrievers, focusing on their immune responses to TLR ligand-induced infections.MethodsThe mRNA and miRNA sequencing were performed separately using the Illumina NovaSeq 6,000 platform (150 bp). The study involved comparing the Control group (i.e., without treatment of any TLR-ligand) with each of the Poly I: C, LPS, and CpG ODN-treated groups for Labrador and Gaddi dogs. Functional enrichment analysis of differentially expressed genes (DEGs) (fold change >3 and <−3, p < 0.05) was conducted to identify enriched pathways in each breed.ResultsThe analysis revealed that Labrador dogs had more DEGs across all treatment groups than Gaddi dogs. The enriched pathways in Labradors included Th1, Th2, Th17 cell differentiation, and T-cell receptor signaling. In contrast, Gaddi dogs significantly enriched ‘Wnt’ signaling, T cell activation, and immune regulation pathways. The differential expression (DE) analysis of miRNA-Seq results indicated that Labradors had more DE miRNAs (with expression levels of the original level >1.5 and <−1.5), such as miR-204, miR-206, miR-106a, miR-132, miR-335, and miR-676, which help regulate inflammation, autophagy, and immune responses. Gaddi dogs had unique miRNAs (miR-551 and miR-1249) associated with tumor suppression and inflammation.DiscussionThe study highlights distinct immunological profiles between Labrador and Gaddi dogs, with no shared genes responding to TLR-ligand stimulation. The functional enrichment of miRNA targets demonstrated consistent regulatory patterns at both the mRNA and miRNA levels. These findings emphasize the importance of preserving the genetic diversity of indigenous Gaddi dogs and utilizing advanced sequencing techniques to explore immunological diversity for disease resistance and the selection of breeding individuals.